Extended‐spectrum β‐lactamase producing Escherichia coli isolated from wild birds in Saskatoon, Canada. (July 2016) - Parker, D.; Sniatynski, M.K.; Mandrusiak, D.; Rubin, J.E.
Abstract: The epidemiology of antimicrobial resistance is extremely complex and involves humans, domestic animals (companion and agricultural) and wildlife. In North America there have been very few investigations targeting antimicrobial‐resistant organisms in wildlife. In this study, we characterized the susceptibility of Escherichia coli isolated from 75 birds including great horned owls, crows and American robins from the region of Saskatoon, Canada. The recovery rate of E. coli varied significantly between species from 44·8% of robins to 92% of crows. The majority (88·2%) of colonized birds carried only pan‐susceptible organisms. Among isolates resistant to at least one antimicrobial, ampicillin resistance was most commonly identified. Three birds carried multidrug‐resistant isolates (resistant to ≥3 drug classes), and extended‐spectrum β ‐lactamase (ESBL)‐producing organisms (CTX‐M‐15 and SHV2a) were grown from two. We identified a significant relationship between the presence of drug‐resistant E. coli and an urban ( vs rural) origin of the bird. Our findings suggest that crows, due to their ubiquity and high rate of colonization with E. coli, may be efficient targets for future resistance surveillance studies targeting urban wildlife. Significance and Impact of the Study: Antimicrobial resistance is a global problem affecting people and animals. Few investigations describing the presence drug‐resistant organisms in wildlife in North America have been published. In this study, resistant Escherichia coli, including extended‐spectrum β ‐lactamase‐producing strains, were isolated from wild birds in the Saskatoon region of Canada. We found that the recovery rate of E. coli varied significantly by species and was highest among crows. There was also a significant association between drug resistance and urban vs rural birds. Our results suggest that crows may be a good target for future studies investigating antimicrobial resistance in urban wildlife. Abstract : Significance and Impact of the Study: Antimicrobial resistance is a global problem affecting people and animals. Few investigations describing the presence drug‐resistant organisms in wildlife in North America have been published. In this study, resistant Escherichia coli, including extended‐spectrum β ‐lactamase‐producing strains, were isolated from wild birds in the Saskatoon region of Canada. We found that the recovery rate of E. coli varied significantly by species and was highest among crows. There was also a significant association between drug resistance and urban vs rural birds. Our results suggest that crows may be a good target for future studies investigating antimicrobial resistance in urban wildlife.